Uczeń zdolny – uczniem ze specjalnymi potrzebami edukacyjnymi? Uczeń ze specjalnymi potrzebami edukacyjnymi – uczniem uzdolnionym? - Chrzanowska, Iwona (Wydawnictwo Naukowe UAM, 2015)
Today most scientists recognize a gifted student as a student with special educational needs. A gifted student has different from their classmates possibilities, expectations and problems. They usually have no problems with school education (at least at the beginning of it), but they often need special support and sometimes even therapeutic intervention. In the context of the problem: SEN – outstanding ability, it is worth considering students with disabilities. Is it possible to treat students with disabilities in Polish schools as gifted persons/children?
A Gifted Student – a Student with Special Educational Needs? Can a Student with Special Educational Needs be a Gifted Student?
Keywords: exceptional talent/special ability; gifted student; special educational needs; disability; school